A Computational Aerodynamic Study of Tandem Rotating Wheels in Contact with the Ground - Rasidi Rasani, Mohammad; Shamsudeen, Azhari; Harun, Zambri; Mohd Faizal Wan Mahmood, Wan (International Journal of Engineering and Technology, 2018)
Wheels have significant impact on noise and drag of road vehicles, which may influence their fuel consumption, emission and comfort. A number of studies have analyzed flow and aerodynamics of isolated wheel in contact with the ground, but limited attention has been given to interaction between wheels. The present study aims to compare the aerodynamics and flow structure between single and tandem wheels. To that end, flow around single and tandem wheels are simulated using a turbulence Scaled Adaptive Unsteady Reynolds Average Navier Stokes (URANS) model. Wheel geometry was based on the actual wheel used in the experiments of Fackrell and Harvey. Flow around single and tandem wheels were examined and compared, along with their respective drag and lift coefficients. Results for single wheel in contact with the ground show good agreement with previous experiments. In the tandem wheel case, the rear wheel exhibits lower drag coefficient (CD = 0.37) and more downforce (lift coefficient CL = -0.14) compared to the front wheel. The present investigation may help to illustrate impact of wheel interaction on their aerodynamics.Â Â